Epidemiological characteristics of motor neuron disease in Chinese patients. (1st April 2014) - Cui, F.; Liu, M.; Chen, Y.; Huang, X.; Cui, L.; Fan, D.; Pu, C.; Lu, J.; Zhou, D.; Zhang, C.; Yan, C.; Li, C.; et al.
<x xml:space="preserve">Abstract</x> Background The epidemiology, diagnosis, and treatment of motor neuron disease (MND) in Chinese patients are ill known. Methods A registered study of 461 MND patients was conducted across 10 facilities in 7 Chinese cities from February 2009 to March 2010. Results Patients were classified as amyotrophic lateral sclerosis (ALS) (84.4%), progressive bulbar palsy (PBP) (4.1%), progressive muscular atrophy (PMA) (10.4%), or primary lateral sclerosis (PLS) (0.9%). MND was predominant in men (men/women; 1.6:1.0). Mean onset age was 52.6 years, with the highest incidence being observed between 51 and 60 years. Notably, 26.0% of MND patients were employed in forestry, fishery, or animal husbandry industries. Ten cases (2.7%) reported family history of MND, and 54.2% exhibited cervical onset. MND was also associated with head/neck trauma. Non‐invasive positive pressure ventilation was the most common supportive therapy. Conclusion As a novel comprehensive report of a Chinese population, this study reveals that epidemiological characteristics of MND patients were similar to those observed in international populations. MND is age‐related, male gender predominant, and may be associated with both environmental and genetic risk factors.